Natural Rights, Under-Specified Rights, and Bills of Rights - Hittinger, Russell (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1998)
The lawers of antiquity defined justice as "giving to each what is his ius [due, right]": ius suum cuique tribuere. Until or unless someone can rightfully claim "that is owed to me [him, or them]" there is no issue of justice. For any practical purpose, the discourse of rights depends on our ability to recognize with some precision who owes what to whom. Bills and charters of rights typically enumerate things which the government owes to citizens or persons. Since World War Two, domestic and international declarations have emphasized obligations of states to recognize human or natural rights. However, these lists often include "rights" which are rather general and under-specified. Under-specified rights have two deleterious consequences for constitutionally limited governments. First, such "rights" inspire the belief that persons have rights prior to anyone knowing precisely what they are. Second, under-specified rights typically burden courts with the task of discovering on a case by case basis the precise nature of the right under dispute. Since bills or charters of rights aim to limit the government, we might doubt whether this purpose is really achieved when the government must specify the right on an ad hoc basis. These problems are investigated in light of U.S. constitutional history.